A novel technique for fabricating high reliable trench DMOSFETs using self-align technique and hydrogen annealing. - Jongdae Kim
A novel technique for fabricating high reliability trench DMOSFETs using three mask layers is realized to obtain cost-effective production capability, higher cell density and current driving capability, and higher reliability. This technique provides a unit cell with 2.3∼2.4 μm pitch and a channel density of 100 Mcell/in2. Specific on-resistance is 0.36 mΩ·cm2 with a blocking voltage of 43 V at a gate voltage of 10 V and 5 A source-to-drain current. The time to breakdown of gate oxide grown on the hydrogen annealed trench surface is much longer than that of oxide grown on a nonhydrogen annealed trench surface.
Keywords: 10 V; 2.3 to 2.4 micron; 43 V; 5 A; Blocking voltage; Cell density; Channel density; Cost-effective production capability; Current driving capability; Gate oxide time to breakdown; Gate voltage; High reliability trench DMOSFETs; Hydrogen annealing; Mask layers; Self-align technique; Source-to-drain current; Specific on-resistance.; Trench surface; Unit cell